Prevalence of injury and utilization of personal protective equipment among building construction workers and associated factors in Bale and West Arsi Zones, southeast Ethiopia 2022 - Aliyi, Ahmednur Adem; Hashim, Mohammed Abdela; Abdurebi, Muhammed Jemal (Frontiers in Public Health, 2024)
Introduction The building construction industry is well known for being one of the most dangerous industries worldwide. Statistics show it is one of the most dangerous occupations in the world. The aim of this study is to assess the prevalence of injury, personal protective equipment usage among building construction workers, and associated factors in Southeast Ethiopia. Methods Institutional-based cross-sectional study was done among 406 selected construction workers in Southeast Ethiopia. Study participants were selected randomly. Data were collected by using a structured questionnaire. Descriptive statistics was used to summarize study variables. Binary logistic regression was utilized to investigate factors associated with injury among study participants. Accordingly, adjusted odds ratio along its 95% confidence interval were calculated and a p value of <0.05 was used to declare statistical significance. Generalized linear models were utilized to investigate factors associated with the use of personal protective equipment. Accordingly, an adjusted odds ratio with a 95% confidence interval was determined and a p value of <0.05 was used as a level to declare a significant statistical association. Result and discussion In this research 406 building construction workers were interviewed and 393 participants gave complete responses, yielding a 96.8% response rate. Of all participants included in this study, 27 (6.8%) drink alcohol and 26 (6.6%) chew khats. Uses of personal protective equipment among study participants was 133 (33.3%, with a 95% confidence interval of 28.3% to 37.7%). Of 393 participants in this study, 213 (54.2%) of them sustained at least one building work-related injury in the last year. The commonest type of injury that occurred among this population was abrasion 43.3% followed by muscular pain (13%). Not having orientation about personal protective equipment, without safety training, didn’t use personal protective equipment, and rural residence were factors significantly associated with injury among building construction workers. Residence, age, monthly income, service year, orientation about personal protective equipment, safety training, and start using personal protective equipment immediately after the job offers were significantly associated with the uses of personal protective equipment by participants of this study. In general, this study has identified a relatively high prevalence of injury and low use of personal protective equipment in the study subjects and associated factors.